2021
DOI: 10.3389/fnins.2021.646914
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Foreign Body Response Induced by Neuro-Implants in Rat Cortices Depleted of Resident Microglia by a CSF1R Inhibitor and Its Implications

Abstract: Inflammatory encapsulation of implanted cortical-neuro-probes [the foreign body response (FBR)] severely limits their use in basic brain research and in clinical applications. A better understanding of the inflammatory FBR is needed to effectively mitigate these critical limitations. Combining the use of the brain permeant colony stimulating factor 1 receptor inhibitor PLX5622 and a perforated polyimide-based multielectrode array platform (PPMP) that can be sectioned along with the surrounding tissue, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(72 citation statements)
references
References 108 publications
(223 reference statements)
8
64
0
Order By: Relevance
“…The electron-dense cytoplasm of these microglia was bordered by a clear plasma membrane and contained rough endoplasmic reticulum, mitochondria and dark inclusions which may plausibly be lysosomes and lipofuscin granules (Figures 3 and 4). In line with Figure 2 and our earlier immunohistological studies (Huang et al 2020;Sharon et al 2021), two weeks post-PPMP implantation, TEM images revealed the presence of astrocyte cell bodies and branches in close proximity to the platform surface and within the platform pores (Figures 3B and 4A). Astrocyte cell bodies could be identified by their pale nuclei that had a thin rim of heterochromatin and pale cytoplasm (Figures 3 and 4A).…”
Section: Insulation Of the Ppmp Implants By Microglia At Two Weeks Post Ppmp Implantationsupporting
confidence: 89%
See 4 more Smart Citations
“…The electron-dense cytoplasm of these microglia was bordered by a clear plasma membrane and contained rough endoplasmic reticulum, mitochondria and dark inclusions which may plausibly be lysosomes and lipofuscin granules (Figures 3 and 4). In line with Figure 2 and our earlier immunohistological studies (Huang et al 2020;Sharon et al 2021), two weeks post-PPMP implantation, TEM images revealed the presence of astrocyte cell bodies and branches in close proximity to the platform surface and within the platform pores (Figures 3B and 4A). Astrocyte cell bodies could be identified by their pale nuclei that had a thin rim of heterochromatin and pale cytoplasm (Figures 3 and 4A).…”
Section: Insulation Of the Ppmp Implants By Microglia At Two Weeks Post Ppmp Implantationsupporting
confidence: 89%
“…PI was selected because it is a biocompatible polymer with a Young’s modulus of 2.5 GP. Importantly, based on studies demonstrating that PI implants can be thin-sectioned for histological examinations (Mercanzini et al, 2007;Mercanzini et al, 2008;Richter et al, 2013;Xie et al, 2014;Boehler et al, 2017;Huang et al, 2020) our laboratory has developed procedures to section implanted gMμE-PPMPs along with the surrounding brain parenchyma for light and transmission electron-microscope (TEM) studies (Huang et al, 2020;Sharon et al, 2021). In the present study, we fabricated 1.7 mm long, 280 μm wide and 16 μm thick nonfunctional gMμE-PPMPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations